Regular gastroscopy and colonoscopy during the evaluation of urachal cancer: do we really need them? - Ming-rui Luo; Tao-nong Cai; Jiang-li Lu; Zhen-hua Liu; Sheng-jie Guo; Zhuo-wei Liu; Kai Yao; Zi-ke Qin; Yun-lin Ye (BMC Cancer, 2023)
Abstract Purpose Urachal cancer is similar to gastrointestinal adenocarcinoma in histology, and gastroscopy/colonoscopy is often administered during perioperative evaluation. However, gastroscopy and colonoscopy have corresponding disadvantages. This study discusses whether gastroscopy/colonoscopy is truly necessary for patients with urachal cancer. Patients and methods A total of 166 bladder adenocarcinoma cases diagnosed at Sun Yat-sen University Cancer Center were retrospectively reviewed and divided into two groups (urachal cancer and nonurachal cancer), and perioperative evaluations were retrieved. Results There were 78 patients with urachal cancer, the median age was 48 years, and 59 were male. Perioperative gastroscopy/colonoscopy revealed 5 intestinal polyps and 1 adenoma during these evaluations, and no primary gastrointestinal cancer was found. Meanwhile, preoperative imaging evaluation did not detect significant gastrointestinal lesions. For 88 patients with nonurachal cancer, including primary bladder adenocarcinoma and metastatic tumors from gastrointestinal cancer, the median age was 56 years, and 64 were male. Preoperative imaging evaluation demonstrated 36 cases of gastrointestinal lesions, and 32 were confirmed by gastroscopy/colonoscopy; the other 4 were negative. Another 4 cases of colon cancer were detected by regular colonoscopy for suspected primary bladder adenocarcinoma. In all, 35 cases of colon cancer and 1 case of gastric cancer were identified by endoscopic examination. The diagnostic consistency of imaging and gastrointestinal endoscopy was favorable (P < 0.001), and the negative predictive value and diagnostic efficiency of imaging were 96.9% and 94.6%, respectively. Conclusions The vast majority of gastrointestinal cancer cases can be identified by assessment of the patient’s clinical symptoms, meticulous physical examination, and imaging evaluation. We recommend that gastroscopy/colonoscopy only be applied to patients with urachal cancer when the above examinations are positive.